ETIKA PERIKLANAN DALAM KAMPANYE POLITIK DIGITAL: STUDI KASUS PEMILU DI INDONESIA 2024 - Yofa Fitriani Zahra; Muhammad Albi Faqih; Ilmi, Maulana Hafidz; Daniel Handoko (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The 2024 General Election in Indonesia marked a significant shift in the landscape of political communication from conventional media to the digital sphere. Political campaigns conducted through social media and online platforms have opened new opportunities for persuasive effectiveness but also introduced serious challenges in terms of communication ethics, particularly in advertising. This study aims to analyze digital political campaign practices during the 2024 election through the lens of the Indonesian Advertising Ethics Code (Etika Pariwara Indonesia/EPI), which serves as a self-regulatory standard in the advertising industry. This research employs a qualitative approach using a case study method, supported by documentation analysis, digital observation, and literature review. The findings reveal that many digital political advertisements violate key EPI principles, including honesty, transparency, and social responsibility. The most prominent violations include negative campaigning, the use of religious symbols to construct candidate images, and undisclosed endorsements by political influencers. Weaknesses in digital monitoring systems exacerbate these issues, allowing unethical content to spread massively and uncontrollably. This study concludes that the implementation of EPI in digital political campaigns remains weak and requires a more adaptive, collaborative, and technology-based monitoring approach to safeguard democratic integrity in the digital communication era.